A survey of fungi at the University of Wisconsin-Waukesha Field Station - (:unkn) unknown (My University, 1993)
A long-term study of higher fungi and Myxomycetes, primarilyfrom the xeric oak woods, was started in 1978. Collections have been made periodically since then, and recent sampling in conifer plantations indicates that characteristic ectomycorrhizal species of Basidiomycetes are beginning to appear in these communities. To date seven Myxomy-cetes, 22 Ascomycetes, and 107 Basidiomycetes have been identifiedfrom various habitats. These data will be incorporated into a master list of fungi generated from long-term surveys at several additional sites in southeastern Wisconsin.
Keywords: fungi; University of Wisconsin-Waukesha Field Station